MODEL KNOWLEDGE SHARING PADA KELOMPOK USAHA BERSAMA (KUB) DI GEMPOL PASURUAN - Rozanatul Maroddah; Laila Ulul Ilmi; Wahyu Eko Pujianto (Universitas Triatma Mulya, 2023)
Joint Business Group (KUB) is an organization as a forum for community empowerment to review economic improvement. This study aims to identify the knowladge sharing model in KUBs in Gempol Pasuruan District Villages with a research sample of 13 villages. The research used a qualitative model with descriptive type. Data collection techniques through observation, interviews, and documentation. The results showed that knowledge sharing in KUBs in Gempol Subdistrict Villages includes: (1) Regular Cadence (RC); (2) Integrating Expertise (IE); (3) Diversity and Inclusion (DI); (4) Regular Knowladge Update (RKU); (5) Interconnected Platforms that are Accessible to all (IPA); and (6) Create Points of Contact within Different Departments of an Organization (CPCDDO)